902. Selection of Antibiotics for Prophylaxis of Left Ventricular Assist Device Surgical Infections: More is Not More. (31st December 2020) - Nguyen, Peter T; Sam, Teena; Colley, Peter; Van Zyl, Johanna; Berhe, Mezgebe; Meyer, Dan
Abstract: Background: Surgical site infections (SSI) for implantation of left ventricular assist devices (LVADs) are associated with high mortality. Updated guidance from the International Society for Heart and Lung Transplant recommends that SSI prophylaxis regimens target Staphylococcus spp and recommend against broad regimens targeting gram-negatives and fungi. The purpose of this study was to compare outcomes between patients that received broad or narrow antimicrobial prophylaxis regimens after a change in institutional protocol. Methods: This single center retrospective study included adult patients who underwent LVAD implantation between January 2015 and September 2019. Patients were excluded if post-surgical care was managed at an outside facility, were treated for an active infection at the time of implantation, or underwent re-implantation within 90 days. The narrow spectrum group consisted of patients that received cefazolin, vancomycin or both, while the broad spectrum group consisted of patients that received an anti-pseudomonal beta-lactam plus vancomycin ± other antibiotics. Data was compared using t-test or Wilcoxon rank sum test, Chi-Square test, or Fisher's Exact. Cox-proportional hazards models and log-rank tests were used for survival analysis. Results: A total of 104 patients were included, with 39 and 65 patients receiving narrow and broad spectrum prophylaxis, respectively. There was no difference in the primary outcome of SSI rate between the narrow and broad antimicrobial prophylaxis groups at 30 days (7.7% vs 7.7%, p=1.00) and 1 year (18.0% vs 18.5%, p=1.00) respectively. Secondary outcomes of time to mortality (HR 0.45, 95% CI 0.15-1.36, logrank P=0.15), time to first infection (HR 0.68, 95% CI 0.26-1.8, logrank P=0.44), or the composite outcome of mortality or infection (HR 0.55, 95% CI 0.24-1.23, logrank P=0.14) were not different between the groups. The majority of infections were due to gram-positive bacteria (73%), most commonly methicillin susceptible S. aureus (36%). Time to Mortality Time to First Infection Composite Outcome (Time to First Infection or Death) Conclusion: This study supports the use of narrow spectrum antimicrobial prophylaxis in LVAD implantation. These results highlight an opportunity to improve antibiotic use in LVAD implantation. Disclosures: All Authors : No reported disclosures